Working poverty in Europe. A comparative approach (New York, 2011)
"This is a study of a complex but important concept, working poverty (or in-work poverty), involving individuals both as workers and members of households. It is caused by low pay, but also weak labour force attachment and high needs. The most recently available version of the household survey, EU-SILC, is analyzed to explain factors behind working poverty in different European countries. There has been a growth of jobs in Europe in the last fifteen years, but this has not decreased poverty because of a relative expansion of low quality jobs. Now economic crisis threatens to increase poverty further. But there is quite a diversity of situations within the EU which this book explores. It includes discussion of working poverty in relation to gender, to migration, and policies like tax-credits. Case studies of UK, France, Spain, Sweden and Poland are included and these countries are given special attention in most of the chapters."